Strengthening control in laser powder bed fusion of austenitic stainless steels via grain boundary engineering. (15th December 2021) - Sabzi, Hossein Eskandari; Hernandez-Nava, Everth; Li, Xiao-Hui; Fu, Hanwei; San-Martín, David; Rivera-Díaz-del-Castillo, Pedro E.J.
Graphical abstract: Highlights: Process/microstructure/strength in laser powder bed fusion are related. Yield strength scales with subgrain size through a Hall–Petch-type relationship. Dynamic recovery is essential to promote low-angle grain boundaries. In situ dynamic recovery and recrystallization modelled via two approaches. Abstract: A new approach to modelling the microstructure evolution and yield strength in laser powder bed fusion components is introduced. Restoration mechanisms such as discontinuous dynamic recrystallization, continuous dynamic recrystallization, and dynamic recovery were found to be activated during laser powder bed fusion of austenitic stainless steels; these are modelled both via classical Zener-Hollomon and thermostatistical approaches. A mechanism is suggested for the formation of dislocation cells from solidification cells and dendrites, and their further transformation to low-angle grain boundaries to form subgrains. This occurs due to dynamic recovery during laser powder bed fusion. The yield strength is successfully modelled via a Hall–Petch-type relationship in terms of the subgrain size, instead of the actual grain size or the dislocation cell size. The validated Hall–Petch-type equation for austenitic stainless steels provides a guideline for the strengthening of laser powder bed fusion alloys with subgrain refinement, via increasing the low-angle grain boundary fraction (grain boundary engineering). To obtain higher strength, dynamic recovery should be promoted as the main mechanism to induce low-angle grain boundaries. The dependency of yield stress on process parameters and alloy composition is quantitatively described.